1985
DOI: 10.1177/153857448501900405
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Platelet Inhibition on the Patency of Femoro-Popliteal Dacron Bypass Grafts

Abstract: Neointimal hyperplasia and thrombosis initiated by platelet activity may contribute to the failure of femoropopliteal Dacron bypass grafts. We have therefore undertaken a randomised prospective double blind trial comparing the efficacy of a combination of acetyl salicylic acid (ASA) 330 mg and dipyrida mole (DPM) 75 mg three times daily, with placebo in maintaining the patency of femoropopliteal Dacron bypass grafts implanted to relieve disabling claudica tion. Patients received either ASA/DPM or placebo comme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
1

Year Published

1986
1986
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 16 publications
0
24
0
1
Order By: Relevance
“…Although the mechanisms of occlusion are multifactorial,' many studies in animals and in humans suggest that platelet accumulation may play a prominent role, either directly by the formation of occlusive thrombus or indirectly by stimulation of intimal hyperplasia. Studies of indium-i 1 1 ("'In)-labeled platelets have documented that platelet deposition is greatest early after arterial graft placement.2' 3 Although deposition decreases in the subsequent 6 months, platelet accumulation remains readily detectable for periods of up to 10 years.4 5 Aspirin plus dipyridamole, used early postoperatively when deposition is maximal, reduces "'In-labeled platelet uptake on Dacron or polytetrafluoroethylene arterial grafts in humans6' 7 and has been associated with improved short-term patency compared with placebo ther-6, [8][9][10] apy.Whether aspirin plus dipyridamole reduces platelet uptake on older grafts that have a lesser rate of platelet deposition, but a continued risk of occlusion, remains unclear. Prior studies have documented that other platelet inhibitory agents, including ticlopidine," suloctidil,'2 and sulfinpyrazone'3 do not reduce platelet accumulation on grafts greater than 9 months old.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the mechanisms of occlusion are multifactorial,' many studies in animals and in humans suggest that platelet accumulation may play a prominent role, either directly by the formation of occlusive thrombus or indirectly by stimulation of intimal hyperplasia. Studies of indium-i 1 1 ("'In)-labeled platelets have documented that platelet deposition is greatest early after arterial graft placement.2' 3 Although deposition decreases in the subsequent 6 months, platelet accumulation remains readily detectable for periods of up to 10 years.4 5 Aspirin plus dipyridamole, used early postoperatively when deposition is maximal, reduces "'In-labeled platelet uptake on Dacron or polytetrafluoroethylene arterial grafts in humans6' 7 and has been associated with improved short-term patency compared with placebo ther-6, [8][9][10] apy.Whether aspirin plus dipyridamole reduces platelet uptake on older grafts that have a lesser rate of platelet deposition, but a continued risk of occlusion, remains unclear. Prior studies have documented that other platelet inhibitory agents, including ticlopidine," suloctidil,'2 and sulfinpyrazone'3 do not reduce platelet accumulation on grafts greater than 9 months old.…”
mentioning
confidence: 99%
“…2' 3 Although deposition decreases in the subsequent 6 months, platelet accumulation remains readily detectable for periods of up to 10 years. 4 5 Aspirin plus dipyridamole, used early postoperatively when deposition is maximal, reduces "'In-labeled platelet uptake on Dacron or polytetrafluoroethylene arterial grafts in humans6' 7 and has been associated with improved short-term patency compared with placebo ther-6, [8][9][10] apy.…”
mentioning
confidence: 99%
“…The first meta-analysis published in 1994, [8] included 11 studies [9][10][11][12][13][14][15][16][17][18][19]. In these studies, allocation to antiplatelet therapy compared to placebo was associated with a proportional reduction of 38% (± 9%) in graft occlusion, which was highly significant [8].…”
Section: A Aspirin (Acetylsalicylic Acid Asa)mentioning
confidence: 98%
“…The Antiplatelet Trialists' Collaboration showed a beneficial effect of aspirin therapy with no clear differences between types of arterial disease. The efficacy of long-term treatment with aspirin in patient's who undergo infrainguinal bypass surgery, however, has been studied in only a few randomised trials [58][59][60][61][62]. The BOA (The Dutch Bypass Oral Anticoagulants or Aspirin) trial showed that VKAs were better for the prevention of infra-inguinal-vein-graft and for lowering the rate of ischemic events.…”
Section: Peripheral Artery Diseasementioning
confidence: 99%